Accuracy of 3D printed models created by different designs of wall thickness - ZHAO Yanfang, ZHANG Chunbao, LIU Huan, LI Kai, XIN Haitao, HU Jiahuan, WU Yulu (Kouqiang yixue)
Objective To study the effect of wall thickness on the accuracy (trueness and precision) of 3D printed models. Methods The 3D scanning data of the standard gypsum dental arch model was imported into Exocad software. And four sets of models were designed, including horseshoe shaped solid model and horseshoe shaped hollow models with different wall thicknesses (2 mm, 3 mm, 4 mm). On the first and seventh day after printing, the 3D scanning data of resin models were imported into Geomagic software. Deviation analysis were performed on 3D printed models for the root mean square (root mean square, RMS). Results The trueness range of the four groups of printed models on the first day was (34.63±4.17)μm to (45.26±6.50)μm, there was no statistical difference. The precision range was (30.25±10.18)μm to (47.65±14.77)μm, and the precision of the solid group was lower than the other three groups (P<0.05). The trueness range of the four groups of printing models on the 7th day was (49.00±9.11)μm to (69.25±9.70)μm. The trueness of the 2 mm wall thickness group was lower than that of the solid group and the 4 mm wall thickness group (P<0.05). Conclusion The accuracy of printing models with different wall thicknesses was within the clinical acceptance range. There was no statistically significant difference in the trueness values of the four groups of printing models on the first day. The precision value of the solid group was the lowest. On the 7th day, the trueness of the wall thickness of 2 mm group was lower than that of the solid group and the 4 mm wall thickness group.